THE INFLUENCE OF OPTICAL CHARACTERISTICS OF A LENS ON THE PERCEPTION OF ARTISTIC IMAGE IN PORTRAIT PHOTOGRAPHY (American Journal of Technology and Applied Sciences, 2025)
This article examines the influence of lens optical characteristics on the perception of artistic imagery in portrait photography. Key parameters are examined: focal length, aperture, depth of field, aberrations, and bokeh, as well as their role in shaping the emotional and visual perception of a portrait. Based on an analysis of experimental shots and viewer assessments, patterns in the influence of optics on the perception of depth, plasticity, and the psychological distance between the model and the viewer are determined. The results demonstrate that the optimal combination of lens technical characteristics enhances the expressiveness of a portrait image and contributes to a more accurate conveyance of the author's artistic intent.